A three-rooted permanent maxillary canine: A rare anatomical variant - Saravanan Kandasamy; Naveen Balakrishnan; Manoj Chandrasekar (Wolters Kluwer Medknow Publications, 2019)
Maxillary canines are usually found to be the single-rooted, single-canaled teeth1. Two roots with two root canals are a very rare condition2. Here we report a rare case of anatomic variation of permanent maxillary canine with three roots and three root canals which is first of its kind in the literature.